Der römische Triumph in Prinzipat und Spätantike - Goldbeck, Fabian; Wienand, Johannes (De Gruyter, 2017)
"The triumphal procession is the most spectacular staging of victory in Roman antiquity and one of the most persistent rituals of any kind. For the first time, this volume systematically explores the historical development and sociocultural meaning of the Roman triumphal procession in the Principate and late antiquity. It casts light on the ritual from a broad range of historical, philological, and archeological perspectives"--Provided by publisher
Enthält Literaturangaben und Indizes
"Hervorgegangen ... aus einer altertumswissenschaftlichen Konferenz zum römischen Triumph in Prinzipat und Spätantike, die vom 4. bis 6. Oktober 2012 im Festsaal der Humboldt Graduate School Berlin stattfand." - (Vorwort)
Keywords: Rome -- History -- Empire, 284-476; Rome -- History -- Empire, 30 B.C.-284 A.D; Rome -- Military antiquities; Konferenzschrift -- 2012 -- Berlin; Geschichte; Triumphzug; Triumph; Römisches Reich